2021
DOI: 10.1038/s41598-021-83895-6
|View full text |Cite
|
Sign up to set email alerts
|

Distinct effects of V617F and exon12-mutated JAK2 expressions on erythropoiesis in a human induced pluripotent stem cell (iPSC)-based model

Abstract: Activating mutations affecting the JAK-STAT signal transduction is the genetic driver of myeloproliferative neoplasms (MPNs) which comprise polycythemia vera (PV), essential thrombocythemia (ET) and myelofibrosis. The JAK2p.V617F mutation can produce both erythrocytosis in PV and thrombocytosis in ET, while JAK2 exon 12 mutations cause only erythrocytosis. We hypothesized that these two mutations activated different intracellular signals. In this study, the induced pluripotent stem cells (iPSCs) were used to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…Current understanding suggests IFN-a-mediated promotion of JAK2 V617F-mutated HSC cell cycle not only exhausts the cells, but uses induces differentiation to the erythroid lineage, making them susceptible to IFN-a-mediated apoptosis (120). Nevertheless, the effects of IFN-a demonstrated here may not be wholly specific to the V617F mutant, since stem cell derived erythrocytes containing JAK2 with exon 12 mutations (also causing constitutive JAK2 activation, as seen in PV) were also sensitive to IFN-a treatment (121).…”
Section: Treating Mpns With Ifnsmentioning
confidence: 83%
“…Current understanding suggests IFN-a-mediated promotion of JAK2 V617F-mutated HSC cell cycle not only exhausts the cells, but uses induces differentiation to the erythroid lineage, making them susceptible to IFN-a-mediated apoptosis (120). Nevertheless, the effects of IFN-a demonstrated here may not be wholly specific to the V617F mutant, since stem cell derived erythrocytes containing JAK2 with exon 12 mutations (also causing constitutive JAK2 activation, as seen in PV) were also sensitive to IFN-a treatment (121).…”
Section: Treating Mpns With Ifnsmentioning
confidence: 83%
“…JAK2V617F-iPSCs did not exhibit a significant increase in erythroid cell proliferation or differentiation, most likely because the studied JAK2V617F expression was more consistent with the heterozygous JAK2V617F mutation in ET patients, where the endogenous JAK2 gene was still present [148,149]. The utilization of different types of JAK2 mutations in patient-derived iPSCs or generated mutant iPSCs for the discovery of pathogenesis and candidate therapy for MPNs has been demonstrated [149,150]. Additionally, hiPSCs derived from patients with the calreticulin (CALR) gene mutation, which is usually found in ET and primary myelofibrosis patients, could reflect disease phenotypes by representing megakaryopoiesis and prominent colony-forming unit megakaryocytes (CFU-MK) [151,152].…”
Section: Acquired Hematologic Disordersmentioning
confidence: 89%
“…JAK2exon12-iPSCs, but not JAK2V617F-iPSCs, exhibited an increased erythropoiesis resembling the pathophysiology in PV patients. JAK2V617F-iPSCs did not exhibit a significant increase in erythroid cell proliferation or differentiation, most likely because the studied JAK2V617F expression was more consistent with the heterozygous JAK2V617F mutation in ET patients, where the endogenous JAK2 gene was still present [148,149]. The utilization of different types of JAK2 mutations in patient-derived iPSCs or generated mutant iPSCs for the discovery of pathogenesis and candidate therapy for MPNs has been demonstrated [149,150].…”
Section: Acquired Hematologic Disordersmentioning
confidence: 94%
“…By contrast, mutations in Jak2 exon 12, which are much rarer than the V617F mutation, are much more specifically associated with PV. Experiments in which both mutations have been introduced in iPSCs have shown that, compared with JAK2V617F-iPSCs, JAK2exon12-iPSCs produced a greater number of erythroid cells that displayed more mature morphology and expressed more adult hemoglobin 50 . Importantly, exon12 mutations led to significantly higher levels of phospho-STAT1 but lower phospho-STAT3 s compared with JAK2V617F-iPSCs in response to erythropoietin.…”
Section: Discussionmentioning
confidence: 99%